Socialization Vigilance Early : Prepare Youth Become Agent Of Change - Ramdanil Mubarok; Moh Tauhid (PT. Sharia Journal and Education Center, 2024)
Early vigilance is key in facing various social, political and economic challenges that continue to develop. Youth have a strategic role as agents of change who can prevent and overcome these threats through awareness and active participation. This service activity aims to increase youth awareness regarding the importance of early awareness, as well as preparing them to take a role in positive social change. Socialization is carried out through a participatory approach, using the Community-Based Research (CBR) method which involves workshops, discussions and simulations based on relevant real situations. The results of this activity show an increase in youth understanding of early warning and their role as agents of change in society. Positive impacts can also be seen from the increasing awareness of local communities regarding the importance of youth involvement in creating a safer and more responsive environment to change. It is hoped that this activity can become a model for developing community service based on youth empowerment to face future challenges.